High Prevalence of Potential Drug-Drug Interactions Among Patients Treated with Off-label Therapies for COVID-19 - Allan Ramos-Esquivel; Cristina Fernández; Luis Garro-Zamora; Ana Victoria Chaves; Álvaro Víquez-Jaikel (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: During the first wave of the COVID-19 pandemic, severe patients were treated with the off-label drugs hydroxychloroquine and lopinavir/ritonavir. The aim of the study was to determine the prevalence of potential drug-drug interactions (DDIs) between hydroxychloroquine, lopinavir/ritonavir and concomitant medications used by hospitalized patients treated for COVID-19 in Costa Rica.Methods: We included all patients that received lopinavir/ritonavir or hydroxychloroquine as treatment for COVID-19. Clinical pharmacists reviewed the prescription profile of each patient and determined the probability and severity of any DDI through two databases (The Lexi-Interact program) and the Micromedex online interaction checker. A logistic regression model was used to identify variables associated with the occurrence of potential DDIs.Results: We identified a total of 108 potential DDIs in 34 inpatients (n=34). At least one of these DDIs occurred in 27 patients (79.4%; 95% CI: 65.8-92.9%). A total of 70 DDIs (64.8%) were classified as clinically relevant (grade D or X) by the clinical pharmacists. Only the number of concomitant drugs was associated with the occurrence of a probable DDI. The most common drugs associated with any DDI were fentanyl (n=12, 11.1%), midazolam (n=11, 10.2%), and insulin (n=10, 10.2%).Conclusion: A large proportion of patients treated with hydroxychloroquine and lopinavir/ritonavir for severe COVID-19 were at risk for clinical meaningful DDIs.